Review of pollutants in urban road dust: Part II. Organic contaminants from vehicles and road management. Issue 4 (2nd October 2019) - Hwang, Hyun-Min; Fiala, Matthew J.; Wade, Terry L.; Park, Dongjoo
ABSTRACT: Urban road dust is highly enriched with organic pollutants such as polycyclic aromatic hydrocarbons (PAHs), petroleum hydrocarbons, and herbicides that are released primarily from vehicles and/or road management practices. Analysis of sediment cores from urban watersheds clearly demonstrates that increase of pollutant input correlates with traffic volume increase. Pollutants in urban road dust are a significant threat to the health of aquatic organisms. Contaminated urban road dust is mobilized by stormwater runoff and transported into local receiving waterbodies (e.g. streams, rivers, lakes, and estuaries). Concentrations of PAHs in sediments receiving stormwater runoff from densely populated urban areas are high enough to impair the health of aquatic organisms and frequently exceed sediment quality guidelines. To restore streams and rivers impaired by roadway runoff, concentrations of pollutants in road dust need to be reduced through implementing a combination of regulatory policies and management actions. One approach would be to phase out existing pollutant sources such instituting a ban on the use of coal tar-based asphalt road seal coat containing high levels of PAHs. Instituting the use of environment friendly natural herbicides with only spot treatment to target weeds rather than broadcast application and restoration of native vegetation, as integrated roadside vegetation management programs. Adoption of these practices would result in significantly reduced herbicide contamination of roadway stormwater runoff. An alternate option is the removal of contaminants from stormwater runoff before they are delivered to receiving waterbodies using best management practices (BMP) such as retention ponds, detention basins, and grass swales. In densely populated urban areas, however, these BMPs may not be easily adopted due to multiple constraints such as lack of spaces and high land cost. In this case, proprietary BMPs such as media filter, wet vault, and vortex separator, which are also known as manufactured treatment devices, can be considered.